Maṣlahah and Justice in the Formulation of the Law: A Critic on the Formulation of Job Creation Law - Desip Trinanda; Abrar Abrar; Muhammad Taufik; Fadhilatul Husni; Diah Febri Utami; Fauzi Yati (Institut Agama Islam Negeri Batusangkar, 2022)
This study aims to explain the process of formulating the Job Creation Law from the prespective of siyāsah tasyri'iyyah. This research is a library research using library collection materials with a descriptive-analytical approach. The result indicates that the principles of the formation of laws and regulations in Siyasah Tasyri'iyyah have not been fulfilled because; First, the presence of the omnibus law method in the process of formulating the Job Creation Law has basically demonstrated the principle of expediency, only that normatively omnibus law has not been regulated in the Law on statutory regulations. Second, the making of the Job Creation Act violates the gradual formation of laws and regulations, it can be seen that the preparation of the Job Creation Act was carried out in a hurry, causing considerable errors. Third, the principle of eliminating difficulties and narrowness has not been fulfilled because it is detrimental to workers. Fourth, the principle of realizing equal justice is not fulfilled, given the limitations in the Job Creation Law which can create legal uncertainty.